Faktor-Faktor yang Mempengaruhi Tenaga Kerja Wanita Menikah Menggunakan Alat Kontrasepsi di Sumatera Barat - Putri Diana Kristina Simatupang; Alpon Satrianto (Jurnal Kajian Ekonomi dan Pembangunan, 2020)
This study aims to determine: (1) the effect of he education level of married women on the use of contraceptives on married women workers in West Sumatra Province. (2) the effect of the  type of work on the  use of contraceptives on married female workers in West Sumatra. (3) the effect in the area of residence on thee use oof contraceptives on thee labor oof married women in West Sumatra.(4) the effect of working hours on the use of contraceptives married female workers in West Sumatra. (5) the effect of income on the use of contraceptives on the labor of woman married in West Sumatera. This research uses data from the National Social Economic Survey (SUSENAS) in 2018. The analysis tool used is logistic regression analysis, and the total number of respondents is 8251 people. The result of the studying indicated that(1) thee level of education has a significant negative effect on the opportunities for married female workers to use contraceptives in West Sumatra, (2) the type of work has no significant negative effect on the opportunities for married womens works to use contraceptives in West Sumatra, (3) the area of residence dooesn’t have a significant positive effect on the opportunities for married female workers to use contraception in West Sumatra, (4) working hours has a siginificant and positive effect on the opportunities for married womens works to use contraception in West Sumatra, (5) income Not a significant positive effect on employment opportunities for married women in using contraceptives in West Sumatra.